1999
DOI: 10.1002/(sici)1097-4644(19990101)72:1<67::aid-jcb8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast markers accumulate on cells developing from human peripheral blood mononuclear precursors

Abstract: Recent studies show that human osteoclasts develop in vitro from hematopoietic cells; however, special cultures conditions and/or cytokine mobilized peripheral blood are apparently required. Here, we report that cells expressing osteoclast markers differentiate from precursors present in nonmobilized peripheral blood mononuclear cells (PBMC), without the addition of stromal cells, growth factors, cytokines or steroids; and characterize their phenotype. Three days after establishing high-density PBMC cultures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 38 publications
6
55
0
Order By: Relevance
“…CD14 þ osteoclast precursors have been shown to lose and acquire macrophage and osteoclast markers respectively in the process of osteoclast differentiation. 14,16 Our findings indicate that the formation of giant cells in ABC is likely to occur by a similar step-wise process from CD14 þ mononuclear phagocyte precursors.…”
Section: Discussionmentioning
confidence: 58%
“…CD14 þ osteoclast precursors have been shown to lose and acquire macrophage and osteoclast markers respectively in the process of osteoclast differentiation. 14,16 Our findings indicate that the formation of giant cells in ABC is likely to occur by a similar step-wise process from CD14 þ mononuclear phagocyte precursors.…”
Section: Discussionmentioning
confidence: 58%
“…15,16 Briefly, PB human CD34 ϩ -enriched stem cells (5 ϫ 10 5 ), obtained by a single leukapheresis of healthy donors treated with granulocyte colony-stimulating factor (G-CSF) for 3 to 5 days, 15 or human PB MNCs at high density (1.5 ϫ 10 6 ), were incubated in a stromal cell-free system with conditioned medium of activated T cells cocultured with HMCLs or purified MM cells in the presence or absence of rhOPG (100 ng/mL and 1 g/mL) or anti-IL-7 polyclonal antibody (0.03 g/mL) or anti-IgG for 10 days. At the end of the culture period osteoclasts (OCs) were identified as tartrate-resistant acid phosphatase (TRAP ϩ ) multinucleated cells (Sigma-Aldrich, Milan, Italy) according to the manufacturer's instructions.…”
Section: Osteoclastogenesismentioning
confidence: 99%
“…Early studies had demonstrated that OCPs originate from the haematopoietic stem cells (Sheven et al, 1986;Hagenaars et al, 1989;Hattersley & Chambers, 1989;Kurihara et al, 1989;Matayoshi et al, 1996) and circulate in PB (Walker, 1973(Walker, , 1975Kahn & Simmons, 1975;Coccia et al, 1980;Faust et al, 1999;. However, whether OCPs possess surface characteristics that distinguish them from other PBMCs (in particular monocytes) is not known.…”
mentioning
confidence: 99%